EXPLORATION OF MARITAL RELATIONSHIP PROJECTS AMONG PARENTS OF A CHILD WITH AN INTELLECTUAL DISABILITY - Fortin, Jean-Simon; Lachance, Lise; Cournoyer, Louis; Lamirande-Landry, Hugo; McKinnon, Suzie; Richer, Louis (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
Parental stress in parents of a child with an intellectual disability may have an impact on their marital relationship. Achievement of marital projects is considered an important factor that sustains marital satisfaction and fulfils the need for relatedness essential to well-being. In this study, which explores marital relationship projects (MRPs) of these parents, 34 couples participated individually in semi-structured interviews using the personal projects analysis grid. In their 5 most important projects, 17 mothers and 17 fathers prioritized at least 1 MRP: mothers in particular reported that they wanted to spend more time with their partners, while fathers wished for opportunities to travel as a couple. The thematic analysis of parents’ appraisals of their MRPs gave rise to 4 categories: “determined optimists”, “determined sceptics”, “postponing optimists”, and “postponing sceptics”. Furthermore, 4 types of conjugal dynamic emerged: “continuity”, “when the time is right”, “it’s getting necessary”, and “it’s complicated”. Gaining knowledge about these parents’ MRPs and how they are appraised will make it possible to offer support and resources that will allow them to pursue their MRPs, leading to more fulfilled relationships.